Dietary Niche Variation in an Invasive Omnivore: The Effects of Habitat on Feral Pig Resource Use in Hawai‘i - Michael S. Peyton; Kealohanuiopuna M. Kinney; Sarah Knox; Grace Tredennick; Sara Hotchkiss (Ecology and Evolution)
ABSTRACT Invasive omnivores may have profound impacts on ecological communities through diet selection, particularly when their functional roles differ from those in their native range. While the threat of feral pigs (Sus scrofa) to native plant communities in Hawai‘i is well known, their trophic dynamics and the drivers of variation in their diet remain understudied. We investigated the feral pig trophic niche on Hawai‘i Island using stable isotopes (13C and 15N) and Bayesian mixing models to identify drivers of variation in resource use. We also reconstructed intra‐individual variability for six subsampled individuals to understand temporal variation in resource use and individual diet specialization. Our results revealed that feral pigs on Hawai‘i Island exhibit a broad trophic niche characterized by diverse diets, with substantial overlap in resource use across districts and habitats. Differences in dietary composition in the transition from forest to open habitat were driven primarily by a decline in invertebrates and an increasing reliance on resources enriched in 15N, which may reflect a shift in protein sources with habitat. Pigs in forested areas exhibited a smaller trophic niche than those in open habitats, largely driven by differences in feeding strategies and resource availability. Diets for subsampled individuals varied little, suggesting feral pig resource‐use strategies in Hawai‘i tend to be relatively stable through time. Individual niche width was relatively narrow compared to that of feral pigs in Hawai‘i at large, indicating the relatively wide feral pig dietary niche is characterized by substantial intraspecific diet specialization, likely as a result of strong intraspecific competition. Understanding the drivers of feral pig resource use offers key information for management strategies aimed at mitigating their ecological impacts in imperiled systems like Hawai‘i.